Caso de negocio para la implementación de un sistema solar fotovoltaico en el supermercado Mercatodo La Floresta (2020)
The main goal of this project is to carry out a feasibility study for the implementation of a photovoltaic solar system in the MERCATODO La Floresta supermarket, located in the city of Cali, Colombia. To achieve this objective, the company?s electrical energy consumption in recent years was characterized, the consumption profile of the different electrical devices used in the operation of the supermarket was elaborated and it was verified that the electrical parameters in the main connection the warehouse comply with current regulations in the country. Next, the climatic, physical, and structural parameters that condition the development of the project were diagnosed, and based on this, the equipment and materials necessary for the implementation of the solar system on the roof of the warehouse were identified, selected and dimensioned. Subsequently, four scenarios were developed, each using different references of photovoltaic modules, to determine through technical and financial analysis which is the most appropriate to implement according to the characteristics of the warehouse and its potential economic return. From the results obtained, it is concluded that from a technical and financial point of view the most convenient scenario is the one that uses monocrystalline photovoltaic modules brand Trina Solar of 410Wp reference TSM-DE15M (II). This is because: it is the case that generates the most photovoltaic energy annually with 214,012 kWh / year and the one with the best financial indicators, with a NPV of COP {dollar} 1,282,440,223, an IRR of 13.74 % and an LCOE of {dollar} 574.96 COP / kWh. Additionally, scenarios with and without the implementation of the project were compared, representing cases with different levels of risk, from which it is concluded that carrying out the project continues to be the most convenient alternative for the company.